Structural evolution and electronic properties of medium-sized boron clusters doped with scandium. (3rd September 2019) - Jin, Siyu; Chen, Bole; Kuang, Xiaoyu; Lu, Cheng; Gutsev, Gennady L
Abstract: Doping of boron-based materials with transition metal atoms allows one to tune or modify the properties and structure of the materials. In this work, an extensive search for the global minima on potential energy surfaces of ScB n and ScB clusters has been performed using the CALYPSO method. The structural evolution of scandium doped boron clusters of this range is found to proceed in three steps; namely, the formation of half-sandwich type structures is followed by the formation of drum-like structures with the Sc atom located at the center and terminates with the cage-like structures. It is also found that highly symmetrical geometric structures are more common for the smaller size range of . The neutral ScB13 cluster is identified as magic on the basis of an analysis of relative stabilities in the ScB n series. Our analysis of chemical bonding has shown that the stability of this cluster is mainly due to the formation of several delocalized -bonding molecular orbitals composed of Sc 3 d and B 2 s atomic orbitals. These bonds appear to be responsible for the enhanced stability of ScB13 with respect to other Sc-doped boron clusters.